Signaling characteristics and functional regulation of delta opioid-kappa opioid receptor (DOP-KOP) heteromers in peripheral sensory neurons. (June 2019) - Jacobs, Blaine A.; Pando, Miryam M.; Jennings, Elaine M.; Jamshidi, Raehannah J.; Zamora, Joshua C.; Chavera, Teresa S.; Clarke, William P.; Berg, Kelly A.
Abstract: Receptor heteromers often display distinct pharmacological and functional properties compared to the individual receptor constituents. In this study, we compared the properties of the DOP-KOP heteromer agonist, 6ʹ-guanidinonaltrindole (6′-GNTI), with agonists for DOP ([D-Pen2, 5]-enkephalin [DPDPE]) and KOP (U50488) in peripheral sensory neurons in culture and in vivo. In primary cultures, all three agonists inhibited PGE2 -stimulated cAMP accumulation as well as activated extracellular signal-regulated kinase 1/2 (ERK) with similar efficacy. ERK activation by U50488 was Gi-protein mediated but that by DPDPE or 6′-GNTI was Gi-protein independent (i.e., pertussis toxin insensitive). Brief pretreatment with DPDPE or U50488 resulted in loss of cAMP signaling, however, no desensitization occurred with 6′-GNTI pretreatment. In vivo, following intraplantar injection, all three agonists reduced thermal nociception. The dose-response curves for DPDPE and 6′-GNTI were monotonic whereas the curve for U50488 was an inverted U-shape. Inhibition of ERK blocked the downward phase and shifted the curve for U50488 to the right. Following intraplantar injection of carrageenan, antinociceptive responses to either DPDPE or U50488 were transient but could be prolonged with inhibitors of 12/15-lipoxgenases (LOX). By contrast, responsiveness to 6′-GNTI remained for a prolonged time in the absence of LOX inhibitors. Further, pretreatment with the 12/15-LOX metabolites, 12- and 15- hydroxyeicosatetraenoic acid, abolished responses to U50488 and DPDPE but had no effect on 6′-GNTI-mediated responses either in cultures or in vivo. Overall, these results suggest that DOP-KOP heteromers exhibit unique signaling and functional regulation in peripheral sensory neurons and may be a promising therapeutic target for the treatment of pain. This article is part of the Special Issue entitled 'New Vistas in Opioid Pharmacology'. Highlights: By contrast to peripheral DOP or KOP: Agonist activation of peripheral DOP-KOP heteromers does not produce desensitization of Gi-protein signaling. Responsiveness of peripheral DOP-KOP heteromers is maintained under prolonged inflammatory conditions. Peripheral DOP-KOP heteromers are resistant to inhibitory effects of LOX metabolites. Peripheral DOP-KOP heteromers may be promising targets for new analgesic drugs.